UPAYA PEMERINTAH KABUPATEN BENGKALIS DALAM PENANGGULANGAN ABRASI (Studi Pada Pesisir Pantai Kabupaten Bengkalis Tahun 2010-2012) - Rahmad Hidayat; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Bengkalis government has the responsibility and authority to abrasion reduction, which is oneform of environmental control that isi part of the area under law No. 32 on 2004 regionalgovernment. With the reduction of abrasion expected Bengkalis coastal areas of abraded toreduce the impact arising from abrasion. But what happens at the moment still found the coastalareas are the still so widely abraded abrasion that is growing every year 7-8 meters/years. Thisis cause of negative impact to survival of society and undermine existing infrastructures. For thegovernment forest rehabilitation and contruction of retaining waves. Also, the governmentshould focus on the preventation of abrasion by allocating sufficient budgeting and more onimproving relationship and good coordination wint the community and coordination amonggovernment agencies that have the same mission in tackling abrasion. However, efforts havebeen good , but not maximized.Keysword: Combating abrasion, coastal, rehabilitation and contruction.